EXPLORING RELIGIOUS AND RITUAL VOCABULARY THROUGH CULTURAL SEMANTICS - Muhammad Natsir (Penelitian dan Pengembangan Ilmu, 2025)
Language reflects cultural values ​​and beliefs, yet thousands of languages ​​are endangered, threatening cultural heritage, including religious and ritual vocabulary. This study explores the role of cultural schemas and conceptual metaphors in shaping the meaning of religious and ritual vocabulary, confirming that religious language is a profound reflection of a community's cultural values ​​and beliefs. Using narrative review Using data from Scopus, Web of Science, LLBA, and Google Scholar, this study analyzes literature published between 2010 and 2025, focusing on cognitive linguistics, cultural linguistics, and language-religion studies. The analytical framework involvesCultural Conceptualization Analysis(CCA) andSemantic Field Analysis. The results indicate that cultural schemas (e.g., purity, sanctity, sacrifice) serve as conceptual frameworks that organize the interpretation of religious terms, distinguishing them from everyday language. Conceptual metaphors, such as